PROBLEMS OF STUDYING THE EMOTIONAL-SEMANTIC LAYER OF SPEECH ACTS - Abduqodirova Madina Abduqayum qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. This study explores the emotional-semantic layer of speech acts, focusing on how emotions and meanings are intricately embedded in verbal communication. The emotional-semantic dimension of speech acts plays a crucial role in understanding the full impact of language on human interaction, as it transcends mere literal meanings to capture the speaker’s emotional state, intentions, and social context. The research examines the theoretical frameworks and methodological approaches used to analyze this layer, highlighting the complexity of verbal communication in different cultural and linguistic settings. Emphasis is placed on the relationship between emotion, meaning, and context, as well as how these elements affect interpretation and communication efficacy. By analyzing speech acts through this emotional-semantic lens, the study aims to contribute to a deeper understanding of pragmatics, discourse analysis, and intercultural communication.